Understanding the continuous vaccination of the COVID-19 vaccine: an empirical study from China - Wenlong Zhu; Hao Zou; Ying Song; Lili Ren; Yingjie Xu (Taylor & Francis Group, 2021)
Vaccination for the novel coronavirus disease 2019 (COVID-19) provides an effective approach for the general improvement of social safety and individual health. However, given that the current COVID-19 vaccine can only work for a period of time, the continuous vaccination of the vaccine will be particularly important. Using the Health Action Process Approach (HAPA) Model, Expectation Confirmation Model (ECM) and vaccine hesitancy (VH) theory, this research evaluates the continuous vaccination for COVID-19. This research selected Chinese survey platform to recruit respondents and conducted online surveys. A total of 768 Chinese individuals who were vaccinated participated in the survey, and 561 responses were effective after screening. Six valuable and novel findings are identified through this research. First, perceived efficacy has a positive significant impact on vaccination intention, but the positive effects of outcome expectancy and risk perception on vaccination intention are not significant. Second, social positive cues play a significant role in promoting vaccination intention. Third, VH has a negative significant influence on vaccination intention. Fourth, vaccination behavior produces a positive significant effect on perceived usefulness and satisfaction, respectively. Fifth, perceived usefulness exerted a positive significant impact on satisfaction and continuous vaccination, respectively. Sixth, satisfaction has no positive significant influence on continuous vaccination. Our theoretical model, which is the main contribution of this research, indicates that individual continuous vaccination is a process from motivation to intention, and from intention to behavior, and then from behavior to continuous vaccination.